Design and Analysis of a Cylindrical Surface Translation and a Rotational Parallel Mechanism - Gao Bo; Shi Zhixin; Luo Yufeng; Lin Hao (Jixie chuandong)
Based on the topology design theory and method of parallel mechanism of position and orientation characteristic (POC) theory, a new 3-DOF parallel mechanism with cylindrical translation and one rotation (2T1R) is designed, and the topological characteristics of the mechanism are analyzed, including the calculation of the position and orientation characteristic set, degrees of freedom and coupling degrees; then the kinematics of the mechanism is analyzed, the forward and inverse solutions of the position of the mechanism are solved and verified; finally, based on the forward and inverse position solutions of the mechanism, the work space and rotation capacity of the mechanism are analyzed. The work of this research lays a foundation for the subsequent scale optimization, error analysis and dynamic analysis of the mechanism.